Analysis of SBR polymer adapted to an automobile damping system - Gil, Adin (Universidad Tecnológica de Panamá, 2015)
To improve the reliability of the damping system of an automobile we investigated a new design which adds a rubber bushing and spring in parallel with the existing spring. This model provides acceptable stiffness values regarding the car suspension. Simulation shows that this model adds a resistance feature to the dynamic constant changes.